Psychological Effects of Language Manipulation in George Orwell’s Animal Farm: A Critical Discourse Analysis Approach - Mutiara Anggela, Ucha; Erlan Aditya Ardiansyah; Wardoyo, Cipto (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2024)
Abstract    This research examines the psychological effects of language manipulation in George Orwell's Animal Farm using Van Dijk's sociocognitive approach. The study explores how language, through strategic manipulation, reinforces social control and psychological subjugation of characters at three levels: micro, meso, and macro. Using in-depth text reading and analysis methods, this study identifies linguistic structures, character interactions, and ideological constructions that contribute to the psychological effects on animals. At the micro level, word choice and sentence structure shape individual perceptions, instilling fear and encouraging obedience. At the meso level, social interactions between characters display emotional manipulation tactics that reinforce collective loyalty and obedience. The macro level highlights ideological changes in social structures, where language systematically conditions characters to accept unjust hierarchies as natural. These manipulative techniques cumulatively suggest that language functions as a tool of psychological control, influencing both individual cognition and collective behavior.